MANAGING THE SPREAD OF COVID-19 PANDEMIC IN INDONESIAN SEA TRANSPORTATION - Utama, I K A P; Setyawan, D; Riyadi, S; Hetharia, W R; Thomas, G A; Ryan, C; Rosa, A G L; Huang, L (Journal of Marine-Earth Science and Technology, 2024)
COVID-19 has been pandemic since the early 2020 and many efforts have been carried out worldwide. Among others, managing the spread of pandemic has been focused on air transportation since the mobility of people has been more actively using aeroplane hence the possibility of infecting people is much higher. Despite less intense, efforts to minimise the blow-out of COVID-19 in sea transportation have also been conducted. The International Maritime Organization (IMO) released guidance such pretravel information to crews and customers The types of guidance include the following items, namely pre-departure, social distancing, the use of masks, personal hygiene, environmental hygiene, and training. In the case of Indonesia, similar direction is introduced and implemented to cargo and passenger vessels. The current paper discusses the Indonesian regulation of managing COVID-19, which is based on IMO/WHO guidance, together with its implementation in the daily activities of people in sea transportation. A survey questionnaire is made out to collect the relevant information. The discussion covers the implementation of such guidance to Indonesian cargo and passenger vessels difficulties in applying the regulation on those ships and the related solutions.